In love with the desert - R. Wheeler (Acta Theologica)
The Christian desert tradition is undeniably male-centred. How the absent feminine paradoxically “appears” in stories and sayings of the tradition can, however, provide an antidote to the otherwise male-centred character of this literature. This article explores how the author, a female researcher of this tradition, has grappled with the tradition’s male-centred character. It demonstrates a hermeneutic of charity requiring creativity to retrieve value from the literature associated with this tradition. It also acknowledges an inspirational encounter with Carmelite spirituality scholar Kees Waaijman that initiated a deepening of the researcher’s commitments to work that matters personally and to others. This article further shows that reading the literature of the Christian desert tradition, alongside contemporary naturalists, reveals ways in which the desert and women’s lives, in particular, have been used, then and now, to reflect on experiences of vulnerability, loss, and discernment of vocation.